Is Seniority-Based Pay Used as a Motivation Device? : Evidence from Plant Level Data - Alberto Bayo-Moriones; José Enrique Galdon-Sanchez; Maia Güell (Institute for the Study of Labor (IZA), 2004)
In this paper we use data from industrial plants to investigate if seniority-based pay is used as a motivational device for production workers. Alternatively, seniority-based pay could simply be a wage setting rule not necessarily related to the provision of incentives. Unlike previous papers, we use a direct measure of seniority-based pay as well as measures of monitoring devices and piece-rates. We find that firms that offer seniority-based pay are less likely to offer explicit incentives. They are also less likely to invest in monitoring devices. We also find that firms that offer seniority-based pay are more likely to engage in other human resource management policies that result in long employment relationships. Overall these results suggest that seniority-based pay is indeed used as a motivation device.
Keywords: M12; M52; J30; 330; human resource management practices; incentives; monitoring; Senioritätsentlohnung; Leistungsanreiz; Ökonomischer Anreiz; Schätzung; Verarbeitendes Gewerbe; Spanien